Factors Related to The Level of Compliance to Pay Contributions of National Health Insurance Participants Non-Wage Earners - Suspamira, Wichsy; Noerjoedianto, Dwi; Amir, Andy; Augina Mekarisce, Arnild; Wardiah, Rizalia (Rifa'Institute, 2023)
Introduction: Nationally, in 2022 there are 15,679,006 participants of Non-Wage Earners in arrears of contributions, while in the working area of BPJS Kesehatan Kambi Branch there are 228,181 participants of Non-Wage Earner Workers in arrears with contributions. The number of participants who are delinquent due to non-compliance of Non-Wage Earner Workers participants in paying contributions. Objective: To measure the relationship between knowledge, number of family members and payment methods with the level of compliance to pay contributions for participants of the National Health Insurance Non-Wage Earner Workers in Jambi City in 2023. Method: This study is a descriptive study with a cross sectional design. Questionnaire research instruments, then univariate and bivariate analysis with chi-square test. Results and Discussion: The results of this study show that there is a significant relationship between knowledge (p-value = 0.000), number of family members (p-value = 0.000) and payment method (p-value = 0.018) with the level of compliance to pay contributions of national health insurance participants non-wage earners workers in Jambi City. Conclusion: there is a relationship between knowledge, number of family members and payment methods with the level of compliance to pay contributions of national health insurance participants non-wage earners workers in Jambi City.